2021
DOI: 10.17323/jle.2021.10296
|View full text |Cite
|
Sign up to set email alerts
|

Exploring How ELT Teachers Perceive and Practice English Language Assessment

Abstract: As a well-designed language education program naturally requires a well-designed assessment component, the pivotal role of assessment in language education needs to be stressed. This study focuses on how English language teaching (ELT) teachers receive training in English language assessment, and how they perceive and practice assessment in Turkey. The study was conducted with the participation of 198 ELT teachers from 24 K-12 level schools and eight universities. A mixed-methods research design was chosen and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…In the literature, a discrepancy is observed between the teachers' perceptions and their LAL-LAK Işık, 2021). Regarding the competency level of the teachers as they perceive themselves to be in assessing each language skill and their actual LAK, the results indicated that, in general, teachers' perceptions are reflected in their knowledge in that they generally felt competent and indicated high LAK level.…”
Section: Discussion Conclusion Recommendationsmentioning
confidence: 83%
See 2 more Smart Citations
“…In the literature, a discrepancy is observed between the teachers' perceptions and their LAL-LAK Işık, 2021). Regarding the competency level of the teachers as they perceive themselves to be in assessing each language skill and their actual LAK, the results indicated that, in general, teachers' perceptions are reflected in their knowledge in that they generally felt competent and indicated high LAK level.…”
Section: Discussion Conclusion Recommendationsmentioning
confidence: 83%
“…It was demonstrated that both pre-and in-service teachers had insufficient knowledge and skills in parallel with their perceptions since they did not feel competent and believed that assessing young learners is a challenging procedure to sustain. On the contrary, in another study with a wider context including primary, secondary, and higher educational context, Işık (2021) found that EFL teachers were confident with their current status even though they indicated low levels of LAL based on data obtained from a questionnaire, interviews, classroom observations, and sample exam evaluations. Concerned with the K-12 context, Ballıdağ and İnan-Karagül (2021) put forth that teachers needed further training due to their insufficient LAL.…”
Section: Literature Reviewmentioning
confidence: 86%
See 1 more Smart Citation
“…Unfortunately, we did not have the opportunity to investigate this due to the small sample size. Other possible reasons, as stated by some researchers (Ghaicha & Omarkaly, 2018;Ghaicha & Oufela, 2021;Isik, 2021;Janisch, Liu, & Akrofi, 2007;Nasri et. al.…”
Section: The Relationship Between Moroccan Efl High School Teachers' Perceptions About Assessment and Their Self-reported Practicesmentioning
confidence: 92%